Profiling microbial populations in various composts - Mou, Wei Bin (Nanyang Technological University, 2020)
Composting is gradually gaining attention given it is an environmentally friendly approach to organic waste disposal with an end product which can be applied to agriculture/horticulture. Numerous researches had begun to study its nutrients and organic matters effectiveness as a soil amendment. Many factors are known to affect the quality of composts, such as raw material and composting methods. This project sets out to compare the chemical and biochemical characteristics of 3 types of composts (black soldier fly compost, ordinary organic compost, and vermicompost). The samples were subjected to pH analysis, total organic carbon and nitrogen analysis, fourier transform infrared spectroscopy, ICP – OES, community level physiological profiling and microbial community profiling based on 16S amplicon NGS analysis. The microbial analysis will shed light on the potential interaction between microbes and plants, hence providing clues to enable future researches to identify plant beneficial microbes for isolation and applications.